Rapid Community Innovation: a Small Urban Liberal Arts Community Response to COVID-19 - Talmage, Craig Allen; Annear, Christopher; Equinozzi, Kate; Flowers, Kathleen; Hammett, Grace; Jackson, Amy; Kingery, Julie Newman; Lewis, Robin; Makker, Kirin; Platt, Audrey; Schneider, Travis; Turino, Caroline (International Journal of Community Well-Being, 2021)
Stories of community resilience and rapid innovation have emerged during the global pandemic caused by COVID-19. As communities, organizations, and individuals have had to shift modalities during the pandemic, they have identified ways to sustain community well-being. Prior to COVID-19, colleges and universities were hailed as anchors of economic and social resilience and well-being for communities of place. In this light, this commentary highlights stories of rapid community innovation occurring at Hobart & William Smith Colleges in the Finger Lakes region of New York. A series of vignettes are presented showcasing lessons and on-going questions regarding rapid pivots, community values, and diversity and inclusion during (and after) the pandemic. Overall, these insights can inform future local collaborative development efforts post-COVID-19 between colleges/universities and their local community.
Keywords: Réservé UdeM; Rôle des universités; États-Unis

Rapid Community Innovation: a Small Urban Liberal Arts Community Response to COVID-19 - Talmage, Craig Allen; Annear, Christopher; Equinozzi, Kate; Flowers, Kathleen; Hammett, Grace; Jackson, Amy; Kingery, Julie Newman; Lewis, Robin; Makker, Kirin; Platt, Audrey; Schneider, Travis; Turino, Caroline (International Journal of Community Well-Being, 2021)
Stories of community resilience and rapid innovation have emerged during the global pandemic caused by COVID-19. As communities, organizations, and individuals have had to shift modalities during the pandemic, they have identified ways to sustain community well-being. Prior to COVID-19, colleges and universities were hailed as anchors of economic and social resilience and well-being for communities of place. In this light, this commentary highlights stories of rapid community innovation occurring at Hobart & William Smith Colleges in the Finger Lakes region of New York. A series of vignettes are presented showcasing lessons and on-going questions regarding rapid pivots, community values, and diversity and inclusion during (and after) the pandemic. Overall, these insights can inform future local collaborative development efforts post-COVID-19 between colleges/universities and their local community.
Number: 3
Keywords: Réservé UdeM; Rôle des universités; États-Unis